Respiratory sound classification : effect of heart sound - Koh, Yong Hui (Nanyang Technological University, 2021)
Singapore has known to be a country with rising amount of population and coupled with a backdrop of ageing population. This proved to be a stress and puts a toll on the medical infrastructure. In a recent study conducted by the Ministry of health, it was revealed that the 2nd most prominent cause for death in Singapore is due to Pneumonia, just behind cancer. [1] Infants and young children, people over the age of 65, and people with chronic disease are at greatest risk of developing severe pneumonia which can be life-threatening. [2]